STUDIES ON PADDY-CUM-FISH CULTURE UNDER DIFFERENT LAND SITUATIONS - KONAR, D.; GHOSH, S. H.; KUNDU, A. L.; BAIRAGYA, C. N.; DATTA, S. K. (Journal of Indian Fisheries Association, 2015)
Paddy fields can be broadly classified on the basis of land situationsviz. Upland - Shallow water (10-30 em), Medium land-medium deepwater(30-100 em) and Low land-deepwater (above 100 em). Three major systemsof paddy-cum-fish culture, viz. (A) high yielding paddy varieties (H.Y.V)and air-breathing fish under Upland, (B) H.Y.V. /local paddy and Tilapia/common carp under Medium land and (C) deepwater paddy and majorIndian carps under Low land situations have been successfullyinvestigated in the farmers' fields and at the Research Stations (1982-92).Effects of low-cost artificial feeding on growth, yield and managementpractices of different types of fish showed a considerable increase of riceand fish yields and a decrease in insect-pest incidence. Under Uplandsituation, short. duration H.Y.V. in combination with fast-growing airbreathingfish were studied thrice a year (summer, winter & autumnseasons). Combined rice and fish culture produced highest yields in allthe seasons than in the control.